General chemistry : - Chang, Raymond (McGraw-Hill, 2008)
Introduction, Atoms, molecules, and ions, Stoichiometry, Reactions in aqueous solutions, Gases, Energy relationships in chemical reaction, The electronic structure of atoms, The periodic table, Chemical bonding I : the covalent bond, Chemical bonding II : molecular geometry and hybridization of atomic orbitals, ...